Heat transfer - Venkateshan, S. P. (Springer, 2021)
The book covers various topics of heat transfer. It explains and analyzes several techniques and modes of heat transfer such as conduction in stationary media, convection in moving media and also by radiation. It is primarily a text book useful for undergraduate and postgraduate students. The book should also interest practicing engineers who wish to refresh their knowledge in the field. The book presents the various topics in a systematic way starting from first principles. The topics are developed to a fairly advanced level towards the end of each chapter. Several worked examples illustrate the engineering applications of the basic modeling tools developed in the text. The exercises at the end of the book are arranged chapter wise and challenge the reader to tackle typical real-life problems in heat transfer. This book will be of potential use for students of mechanical engineering, chemical engineering and metallurgy in most engineering colleges.